2017
DOI: 10.1152/ajprenal.00118.2017
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 attenuates apoptosis of tubular epithelial cells in renal ischemia-reperfusion injury

Abstract: Uncoupling protein-2 (UCP2) plays critical roles in energy metabolism and cell survival. Previous investigations showed that UCP2 regulated the production of extracellular matrix and renal fibrosis. However, little is known about UCP2 in acute kidney injury (AKI). Here, we used knockout mice to investigate the role of UCP2 in an AKI model generated by renal ischemia-reperfusion (I/R) injury. The global knockout mice were born and grew normally without kidney histological abnormality or renal dysfunction. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…UCP2 expression increased about three‐fold in renal tissue of LV‐ Ucp2 (Figure A) and CLA‐fed (see supplementary material, Figure A) mice compared with control mice. Immunostaining showed that UCP2 was expressed mainly in tubular epithelial cells, as previously reported and the tubular expression of UCP2 was markedly increased after lentivirus‐mediated gene transfection (Figure B). In AKI mice, both LV‐ Ucp2 and CLA‐fed restored renal function, evaluated as by BUN and Scr (Figure C and see supplementary material, Figure B) and ameliorated tubular injury in terms of reduction of tubular cell degeneration and necrosis (Figure D and see supplementary material, Figure C).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…UCP2 expression increased about three‐fold in renal tissue of LV‐ Ucp2 (Figure A) and CLA‐fed (see supplementary material, Figure A) mice compared with control mice. Immunostaining showed that UCP2 was expressed mainly in tubular epithelial cells, as previously reported and the tubular expression of UCP2 was markedly increased after lentivirus‐mediated gene transfection (Figure B). In AKI mice, both LV‐ Ucp2 and CLA‐fed restored renal function, evaluated as by BUN and Scr (Figure C and see supplementary material, Figure B) and ameliorated tubular injury in terms of reduction of tubular cell degeneration and necrosis (Figure D and see supplementary material, Figure C).…”
Section: Resultssupporting
confidence: 83%
“…The protective role of autophagy was further confirmed in autophagy‐deficient mice . Currently, the protective role of UCP2 on I/R‐induced AKI by promoting autophagy and protecting renal tubule cells from apoptosis was established by the tests of UCP2‐deficient mouse models . In renal pathophysiology, the information about mitochondrial priming for mitophagy is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-MA is usually used to inhibit and study the mechanism of autophagy. 44 As shown in Figures 6A and 6B, the level of perivascular fibrosis and tubulointerstitial injury score increases after Aldo treatment, whereas SB-216763 can reverse the alteration. More important, pharmacological inhibition of autophagy by 3-MA markedly inhibits the role of SB-216763 in suppressing perivascular fibrosis and tubulointerstitial injury.…”
Section: Sb-216763 Suppresses Aldo-induced Cardiorenal Injury By Rementioning
confidence: 82%
“…An increase in ROS formation in the mitochondria activates UCP2, dissipating the proton motive force as heat and, as a result, reducing ROS production 36,37 . As ROS production contributes to mitochondrial dysfunction in AKI and diabetic nephropathy, UCP2 has been explored in the kidney and in these disease states 38 . Studies investigating the role of UCP2 polymorphisms in the kidney that exacerbate disease in patients with diabetic nephro pathy reveal that UCP2 is a potential target for treatment 39 .…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Studies investigating the role of UCP2 polymorphisms in the kidney that exacerbate disease in patients with diabetic nephro pathy reveal that UCP2 is a potential target for treatment 39 . Lack of UCP2 has also been shown to worsen tubular injury after induction of experimental AKI in mice 38 . These studies show the importance of UCP2 in the kidney as well as its role in attenuating excessive ROS production.…”
Section: Mitochondrial Functionmentioning
confidence: 99%